HEAVINESS OF HAIR PIGMENTATION AND REPRODUCTIVITY IN SABLES (MARTES ZIBELLINA L.) - S. N. Kashtanov; O. E. Lazebny; A. P. Njukhalov; I. E. Chernova; G. P. Svisheva; O. V. Trapezov (Вавиловский журнал генетики и селекции)
Consequences of directional selection for fur blackening were studied in a captive sable population (Pushkinskoe fur farm, Moscow oblast). Crosses of four types were analyzed, in which males and females differed from each other in head fur color. Quantitative traits expressed as indices of reproduction: female fertility, average number of puppies per mated female, average number of puppies per whelped female, and mated but not fertilized females, were compared among the crosses. The lowest indices of reproduction were recorded when females and males with the most blackened fur were crossed. Reproduction indices were evaluated by two-way ANOVA. The results showed that the type of crossing (factor 1) significantly influenced all traits studied. The year of selection period (factor 2) was also significant for all traits, and the interaction of these two factors significantly influenced only one trait, «number of puppies per mated female». As a whole, positive dynamics of these traits was observed over a decade. Therefore, we presume that the continuation of artificial directional selection for sable fur blackening is promising. The main stages of the breeding are recognized, and further actions are outlined.